Cysteine-Rich Secretory Proteins (CRISP) and their role in mammalian fertilization - Cohen, Debora Juana (2011)
Epididymal protein CRISP1 is a member of the CRISP (Cysteine-RIch Secretory proteins) family and is involved in sperm-egg fusion through its interaction with complementary sites on the egg surface. Recent results showed that this binding ability resides in a 12-amino-acid region corresponding to a highly conserved motif of the CRISP family, named Signature 2 (S2). In addition to this, recent results revealed that CRISP1 would also be involved in the previous step of sperm binding to the zona pellucida, identifying a novel role for this protein in fertilization. As another approach to elucidate the participation of CRISP1 in fertilization, a mice line containing a targeted disruption of CRISP1 was generated. Although CRISP1-deficient mice exhibited normal fertility, CRISP1-defficient sperm presented a decreased level of protein tyrosine phosphorylation during capacitation, and an impaired ability to fertilize both zona-intact and zona-free eggs in vitro, confirming the proposed roles for the protein in fertilization. Evidence obtained in our laboratory indicated that testicular CRISP2 would also be involved in sperm-egg fusion. Competition assays between CRISP1 and CRISP2 as well as the comparison of their corresponding S2 regions suggest that both proteins would bind to common complementary sites on the egg. Together, these results suggest a functional cooperation between CRISP1 and CRISP2 to ensure the success of fertilization.